2013
DOI: 10.1002/jobm.201200574
|View full text |Cite
|
Sign up to set email alerts
|

Stress and development in Dictyostelium discoideum: the involvement of the catalytic calcineurin A subunit

Abstract: Calcium signaling is one of the most important signaling-pathways in all eukaryotes. One important target activated by an increased intracellular calcium concentration via calmodulin is the protein phosphatase calcineurin, which is composed of a catalytic subunit (calcineurin A) and a regulatory subunit (calcineurin B). The importance of calcium and calcineurin for the differentiation and development of the social amoeba Dictyostelium discoideum has already been shown by pharmacological approaches. However, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…It has been shown in virulence assays that Crz1 has a moderate effect on virulence whereas calcineurin is essential in a mouse model of infection (22). However, this discrepancy in the phenotypical outcome of mutations of calcineurin and its downstream targets has also been observed frequently in other studies (5,14,31,70) and shows that calcineurin has other targets apart from Crz1. Crz1 is also involved in virulence in other Candida species.…”
Section: Calcineurin-crz1 Signaling and Virulencementioning
confidence: 94%
See 2 more Smart Citations
“…It has been shown in virulence assays that Crz1 has a moderate effect on virulence whereas calcineurin is essential in a mouse model of infection (22). However, this discrepancy in the phenotypical outcome of mutations of calcineurin and its downstream targets has also been observed frequently in other studies (5,14,31,70) and shows that calcineurin has other targets apart from Crz1. Crz1 is also involved in virulence in other Candida species.…”
Section: Calcineurin-crz1 Signaling and Virulencementioning
confidence: 94%
“…As stated above, in addition to the fungal kingdom, calcineurin has been investigated in other lower eukaryotes such as social amoebae (4,5), various parasites (6-8, 11), and amoeboflagellates (97) and in Paramecium (12).…”
Section: Calcineurin-crz1 Signaling Beyond the Fungal Kingdommentioning
confidence: 99%
See 1 more Smart Citation
“…Since CanA, the sole CaM‐dependent protein phosphatase, dephosphorylates both serine and threonine residues, it was suggested that it could function during folic acid‐mediated chemotaxis. CanA was the first CaMBP to be characterized in D. discoideum (Catalano & O'Day, ; Damman et al ., Dammann et al, ; Thewes et al, ). However, despite its role in a diversity of chemotactic events in other species, investigations into the role of CanA suggest it is not linked to folic acid‐mediated chemotaxis.…”
Section: Cell Motility and Chemotaxis During Growthmentioning
confidence: 99%
“…However, to the best of our knowledge, they do not appear to affect calcineurin, and thus, their precise mechanism of action remains to be elucidated. 39,40 A commonly used drug, FK506 (also known as tacrolimus), indirectly inhibits calcineurin activity by binding to a separate protein, FKBP, together forming a potent antagonist. 27 Interestingly, the Legionella protein Mip (macrophage infectivity potentiator) shares structural similarity to the FKBP protein family, and Mip proteins are also known to bind FK506.…”
Section: ■ Discussionmentioning
confidence: 99%